2011
DOI: 10.1186/1471-2318-11-6
|View full text |Cite
|
Sign up to set email alerts
|

A multi-faceted intervention to implement guideline care and improve quality of care for older people who present to the emergency department with falls

Abstract: BackgroundGuidelines recommend that older people should receive multi-factorial interventions following an injurious fall however there is limited evidence that this is routine practice. We aimed to improve the delivery of evidence based care to patients presenting to the Emergency Department (ED) following a fall.MethodsA prospective before and after study was undertaken in the ED of a medium-sized hospital in Perth, Western Australia. Participants comprised 313 community-dwelling patients, aged 65 years and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 30 publications
(39 reference statements)
3
50
0
Order By: Relevance
“…Sports activity was practiced by 22% of our population, and walking accounted for 91%. This rate is comparable to that obtained by Diallo [17] who found that 80% of the patients had walked once or several times a week. In fact, walking is a simple and accessible physical activity for the elderly, and it can be done in the neighborhood or even at home.…”
Section: Lifestyle and Physical Activitysupporting
confidence: 88%
“…Sports activity was practiced by 22% of our population, and walking accounted for 91%. This rate is comparable to that obtained by Diallo [17] who found that 80% of the patients had walked once or several times a week. In fact, walking is a simple and accessible physical activity for the elderly, and it can be done in the neighborhood or even at home.…”
Section: Lifestyle and Physical Activitysupporting
confidence: 88%
“…An initial starting point may be to evaluate current practice against international standards for falls management (NICE, 2004;Salter et al, 2006). But real changes in practice in this area requires a multidisciplinary approach and the development of protocols that include the implementation of evidenced based falls assessment tools and clear referral pathways (Hastings and Heflin, 2005;Waldron et al, 2011). ED nursing staff are in a position to take a critical lead role in driving such an evaluation and practice changes.…”
Section: Implications For Practicementioning
confidence: 99%
“…Multifactorial interventions have been shown to improve the outcome of people who have fallen who are seen and treated in ED [31] and a recent study undertaken in the UK provides evidence that an intervention offered to non-conveyed people who have fallen can make a significant and positive difference to patient health outcomes [12].…”
Section: Alternate Care Pathways For Non-transported Older People Whomentioning
confidence: 99%